2018
DOI: 10.1016/j.chaos.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Non-identical multiplexing promotes chimera states

Abstract: We present the emergence of chimeras, a state referring to coexistence of partly coherent, partly incoherent dynamics in networks of identical oscillators, in a multiplex network consisting of two non-identical layers which are interconnected. We demonstrate that the parameter range displaying the chimera state in the homogeneous first layer of the multiplex networks can be tuned by changing the link density or connection architecture of the same nodes in the second layer. We focus on the impact of the interco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…In particular, the impact of strong multiplexing, when the strength of the coupling between the layers is comparable with that inside each layer, has been investigated for coupled chaotic maps 33,34 . In more detail, it has been shown that strong multiplexing can be used to control chimeras in networks of coupled chaotic maps 34 . The impact of strong multiplexing with an uncoupled layer has been investigated for a network of Hindmarsh-Rose neurons in 35 , where the strong inter-layer links represent chemical connections and weak intra-layer couplings model electrical synapses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the impact of strong multiplexing, when the strength of the coupling between the layers is comparable with that inside each layer, has been investigated for coupled chaotic maps 33,34 . In more detail, it has been shown that strong multiplexing can be used to control chimeras in networks of coupled chaotic maps 34 . The impact of strong multiplexing with an uncoupled layer has been investigated for a network of Hindmarsh-Rose neurons in 35 , where the strong inter-layer links represent chemical connections and weak intra-layer couplings model electrical synapses.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the case of the multilayer brain network, physical connections may be adjustable while the manipulation of the functional connectivity is much more complicated. Although the phenomenon of synchronization 30,[38][39][40][41] and formation of partial synchronization patterns [28][29][30][31]33,34,[42][43][44] have been recently considered in multilayer networks, the challenging problem of controlling chimeras by weak multiplexing, in particular, in neuronal networks has not been yet investigated.…”
Section: Introductionmentioning
confidence: 99%
“…One of an inexhaustible area of research is connected with nonlinear ensembles with a large number of elements and different network topologies, which give rise to various types of spatiotemporal dynamics. Thus, besides widely considered chimera states (see, for example, [1][2][3][4][5][6][7][8][9][10][11][12]), ensembles with nonlocal coupling can demonstrate another, recently found spatio-temporal structure, which is called "solitary state" [7-9, 11, 13-21]. In contrast to the chimera state (which consists of spatially divided clusters of coherent and incoherent behaviour), the solitary state regime is characterized by a coherent behaviour of the whole system, except several elements.…”
Section: Introductionmentioning
confidence: 99%
“…In neuroscience, multilayer networks represent for instance neurons in different areas of the brain, neurons connected either by a chemical link or by an electrical synapsis, or the modular connectivity structure of brain regions [43][44][45][46][47][48][49][50][51]. A special case of multilayer networks are multiplex topologies, where each layer contains the same set of nodes, and only pairwise connections between corresponding nodes from neighbouring layers exist [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71].In spite of the lively interest in the topic of adaptive networks, little is known about the interplay of adaptively coupled groups of networks [25,72,73]. Such adaptive multilayer or multiplex networks appear naturally in neuronal networks, e.g., in interacting neuron populations with plastic synapses but different plasticity rules within each population [74,75], or affected by different mechanisms of plasticity [76], or the transport of metabolic resources [77].…”
mentioning
confidence: 99%